Taxing Pensions - Helmuth Cremer; Pierre Pestieau (Institute for the Study of Labor (IZA), 2016)
There exists a wide variety of tax treatments of pensions across the world. And the reasons for such a range of regimes are not clear. This note reviews the general principles of pension taxes and analyses the theoretical foundations of why pension incomes ought to be taxed specifically. To do this, one has to distinguish between public and private pensions. The design of public pensions cannot be separated from the one of taxation. Regarding private pensions, the key issue is whether or not pension saving ought to be treated differently from other forms of saving.
Keywords: H21; H55; 330; private pensions; deferred tax; social security; retirement